Decomposition rate and biochemical fate of carbon from natural polymers and microplastics in boreal lakes - Vesamäki, Jussi S.; Nissinen, Riitta; Kainz, Martin J.; Pilecky, Matthias; Tiirola, Marja; Taipale, Sami J. (Frontiers in Microbiology, 2022)
Microbial mineralization of organic compounds is essential for carbon recycling in food webs. Microbes can decompose terrestrial recalcitrant and semi-recalcitrant polymers such as lignin and cellulose, which are precursors for humus formation. In addition to naturally occurring recalcitrant substrates, microplastics have been found in various aquatic environments. However, microbial utilization of lignin, hemicellulose, and microplastics as carbon sources in freshwaters and their biochemical fate and mineralization rate in freshwaters is poorly understood. To fill this knowledge gap, we investigated the biochemical fate and mineralization rates of several natural and synthetic polymer-derived carbon in clear and humic lake waters. We used stable isotope analysis to unravel the mineralization processes of different 13C-labeled substrates (polyethylene, polypropylene, polystyrene, lignin/hemicellulose, and leaves (Fagus sylvatica)). We also used compound-specific isotope analysis and molecular biology to identify microbes associated with used substrates. Leaves and hemicellulose were rapidly decomposed compared to microplastics which were decomposed slowly or below detection level. Furthermore, aromatic polystyrene was degraded faster than aliphatic polyethylene and polypropylene. The major biochemical fate of decomposed substrate carbon was in microbial biomass. Bacteria were the main decomposers of all studied substrates, whereas fungal contribution was poor. Bacteria from the family Burkholderiaceae were identified as potential leaf and polystyrene decomposers, whereas polypropylene and polyethylene were not decomposed.